Puzzle: Harvest Time - Gavrilov, Oleg (Dedham, MA : Garden Alive, Inc.)
Oleg Gavrilov's delightful puzzle captures a bustling farmyard scene centered around a vibrant turquoise truck loaded with fresh produce, pumpkins, and sunflowers. Surrounding the truck are playful dogs, chickens, and colorful flowers, creating a lively atmosphere filled with the charm of rural life. In the background, a picturesque red barn and golden fields complete the idyllic farm setting. This puzzle is a celebration of nature's bounty and the joy of country living, perfect for puzzle enthusiasts who love farm-inspired designs.